AI in Education: Revolutionizing Personalized Learning Experiences - Nur Wulandani; Yafita Arfina Mu’ti; Risa Alfiyah Ulfa (EDUJAVARE: International Journal of Educational Research, 2024)
The rapid adoption of artificial intelligence (AI) technologies in education presents opportunities and challenges for personalized learning. Despite its potential to adapt to diverse student needs, integrating AI into educational systems has been met with barriers such as inadequate infrastructure, teacher preparedness, and ethical concerns regarding data privacy and algorithmic bias. This study explores the impact of AI-driven personalized learning tools in secondary and higher education institutions, evaluating their effectiveness and the challenges educators and students face. Using a qualitative research approach, the study employed semi-structured interviews, focus group discussions, and document analysis across five educational institutions in Indonesia. The findings reveal that AI tools can potentially enhance personalized learning, significantly improving engagement and academic performance. However, challenges such as insufficient teacher training, infrastructure limitations, and concerns over data privacy were identified as critical barriers to successful implementation. The study concludes that AI in education can offer transformative benefits, but comprehensive support systems, including teacher training, improved infrastructure, and ethical considerations, must accompany its adoption. This research contributes to understanding how AI can be effectively integrated into education and provides valuable insights for policymakers, educators, and technology developers.